Banking Systems Around the Globe : Do Regulation and Ownership Affect the Performance and Stability? - Barth, James R.; Caprio, Gerard, Jr.; Levine, Ross (World Bank, Washington, DC, 2014)
The authors report cross-country data on commercial bank regulation and ownership in more than 60 countries. They evaluate the links between different regulatory/ownership practices in those countries and both financial sector performance and banking system stability. They document substantial variation in response to these questions: Should it be public policy to limit the powers of commercial banks to engage in securities, insurance, and real estate activities? Should the mixing of banking and commerce be restricted by regulating commercial bank's ownership of non-financial firms and non-financial firms' ownership of commercial banks? Should states own commercial banks, or should those banks be privatized? They find: 1) There is no reliable statistical relationship between restrictions on commercial banks' ability to engage in securities, insurance, and real estate transactions and how well-developed the banking sector, how well-developed securities markets and non-bank financial intermediaries are, or the degree of industrial competition. Based on the evidence, it is difficult to argue confidently that restricting commercial banking activities benefits-or harms-the development of financial and securities markets or industrial competition. 2) There are no positive effects from mixing banking and commerce. 3) Countries that more tightly restrict and regulate the securities activities of commercial banks are substantially more likely to suffer a major banking crisis. Countries whose national regulations inhibit banks' ability to engage in securities underwriting, brokering, and dealing--and all aspects of the mutual fund business--tend to have more fragile financial systems. 4) The mixing of banking and commerce is associated with less financial stability. The evidence does not support admonitions to restrict the mixing of banking and commerce because mixing them will increase financial fragility. 5) On average, greater state ownership of banks tends to be associated with more poorly developed banks, nonbanks, and stock markets and more poorly functioning financial systems.